Plan de Salvaguardia del Patrimonio Cultural Inmaterial de la Parroquia la Providencia del Cantón Guano - Zumba Real, Pamela Estefanía (2019)
The present research project entitled: plan for the safeguarding of the intangible cultural heritage of the La Providencia del Cantón guano parish, has as its purpose the design of the safeguard plan to conserve cultural manifestations through the formulation of the problematic, state of the art, methodology and design of the components of the safeguard plan; where programs and projects emphasized to all the inhabitants of the parish, were established especially to young children, and young adults, in order to maintain their cultural identity, in this way national and international local tourism could be enhanced. The socio-cultural diagnosis revealed important aspects for the identification and conservation of the manifestations, thus enriching the situational analysis of cultural resources, identifying 18 manifestations, interpreting the results, it was possible to verify 8 manifestations with a High score and 5 with a score Low, with these results we proceeded to formulate the strategic philosophical approach starting with the FODA Matrix of the parish, identifying the critical knots and the key success factors of the matrix, With the elaboration of these parameters it was possible to determine the strategies that should be used in the safeguard plan. Finally, the programs and projects that would last for a year and an established budget were carried out. These projects will promote cultural tourism within the parish, thus encouraging all the inhabitants.